2022
DOI: 10.1088/1361-6595/ac9b8d
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of ion and electron flux ratio at their respective sheath-edges and absence of the electron Bohm criterion effects

Abstract: A recent theory suggest that electrons enter electron sheaths at an electron Bohm velocity given by (Te/me)1/2 instead of the electron thermal velocity as conventionally assumed. To test this theory, the flux density ratio Γe,se/Γi,se of electrons and ions entering their respective sheaths was directly measured via an almost continuous Ai/Ae area ratio scanning. The measured value agrees with the predictions assuming electrons entering the electron sheaths at their thermal velocity. The predictions associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…They analyzed each I-V trace and obtained variation of the saturation current with the changes of A L /A S . They concluded that (A L /A S ) crit,Ar is ∼180 for argon plasma, as shown in figure 4, which is consistent with the conventional theory prediction that ions enter the ion sheath with the ion Bohm criterion and electrons enter the electron sheath randomly at electron thermal velocity, given that (A L /A S ) crit = (m i /(2.3m e )) 1/2 [23].…”
Section: Experimental Studies On the Area Limitation Of The Langmuir ...supporting
confidence: 77%
See 2 more Smart Citations
“…They analyzed each I-V trace and obtained variation of the saturation current with the changes of A L /A S . They concluded that (A L /A S ) crit,Ar is ∼180 for argon plasma, as shown in figure 4, which is consistent with the conventional theory prediction that ions enter the ion sheath with the ion Bohm criterion and electrons enter the electron sheath randomly at electron thermal velocity, given that (A L /A S ) crit = (m i /(2.3m e )) 1/2 [23].…”
Section: Experimental Studies On the Area Limitation Of The Langmuir ...supporting
confidence: 77%
“…Yip et al discovered that even when the ratio of the area of the Langmuir probe area to the chamber wall area A L /A S is less than or near (m i /(2.3m e )) 1/2 as predicted by conventional theory, a small virtual cathode can still form near the probe, affecting the I-V curve and leading to a significant error of ∼30% in electron temperature measurement [35]. Jin et al later conducted experiments in Diagnostics Test Source II (DTS-II) [23,36], as shown in figure 3(a), in argon plasma and scanned A L /A S of an ADLP ranging from 15-365 with the 2 mm diameter small probe A S unchanged and the diameter of large probe A L varying from 8-40 mm. The plasma parameters were measured by a single Langmuir probe biased with respect to the grounded chamber wall and the ADLP is floating and its two probe tips were biased with respect to each other, as shown in figures 3(b) and (c).…”
Section: Experimental Studies On the Area Limitation Of The Langmuir ...mentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 3 shows the resultant effective electron temperature T eff obtained by analyzing simulated I-V traces of the ADLP and the EDLP with a typical bi-temperature Maxwellian EEDF analysis method [14,23,[33][34][35][36][37], benchmarked with the real T eff adapted in these computations. It can be shown that even when I L,is > I S,es , i.e.…”
Section: Adlp and Edlpmentioning
confidence: 99%
“…As micro-satellites become increasingly popular in space-probing missions, the area of single Langmuir probes to be installed in these satellites is expected to be limited with increasing severity. The use of symmetric DLPs instead of single Langmuir probes has been adapted in some satellite designs to mitigate this problem [12,13], but the signal quality of DLPs is limited by their ion saturation current [14], and they often have issues resolving an accurate EEDF in the presence of energetic electrons [23].…”
Section: Introductionmentioning
confidence: 99%